The Discrediting of Competing Trademarks - Between Multiple Qualification Option and Qualification Impediment - Iulian MORARU (Eastern European Journal of Regional Studies, 2021)
Discrediting competing trademarks consists in the spread of certain information regarding the trademarks owned by the competitor of the undertaking realizing the disparaging actions. Relating the idea to the legislative provisions in force of the Republic of Moldova, it can be inferred that there are two options for qualifying such a conduct - according to the rules of unfair competition and in accordance with the rules of dishonest advertising. In such circumstances, the obvious question raised is whether the qualification will be done in accordance with one or another relevant legal norm. This aspect requires a broad clarification in the sense of offering viable alternative solutions and corresponding to the various practical factual situations. In this context, it is necessary to establish defined criteria in material and procedural terms in order to achieve a clear delimitation between different qualifying vectors. Circumstantially, there is a need to resort to the approach of domestic practice in this matter, as well as to the treatment of legislative, theoretical and practical trends in other states and legal systems.